Empowered by data : how to build inspired analytics communities - Murray, Eva Katharina, 1985- (Wiley, 2021)
"Tens of thousands of organizations have adopted data analytics tools and processes in the past five to ten years. Some have been extremely successful in growing their user base and giving many of their staff access to these tools so they can contribute to building data-driven organizations by engaging with data, finding insights, and communicating them to their stakeholders. These businesses and nonprofits rely on using data to keep up with the market, the competition, and the needs of the societies around them. For these organizations and the people within them, the concept of building analytics communities, whether they involve three or 300 people, can help to truly engage people at a professional level, drive productivity, and ensure ongoing improvement and development, all while producing real outputs that benefit the bottom line and are critical for achieving their mission. However, some organizations have struggled to maximize their investment in analytics, in the tools they purchased, the processes they created, and the people they hired. How to Build a Data Community addresses this problem and teaches organizations how to create and maintain successful data communities"--